Atypical Blue Rubber Bleb Nevus in an African-American Male - Harpreet S. Gill; Paul Beinhoff; Sarah Grond; Mohan S. Dhariwal; Pinky Jha (Case Reports in Gastrointestinal Medicine)
Blue Rubber Bleb Nevus Syndrome (BRBNS), also known as Bean Syndrome, is a rare condition characterized by vascular ectasias that typically present systemically. Most diagnoses are made in early childhood due to cutaneous lesions in Caucasians with familial inheritance. Treatment is usually patient centered due to the wide variance in clinical presentation of the disease. Here, we present a case of BRBNS in a 65-year-old African-American patient with episodic gastrointestinal (GI) bleeding with no previous history. This case emphasizes the need for a higher clinical suspicion of the disease in patients with recurrent GI bleeding.